Nanostructured metal‐doped Prussian blue thin film electrodes for efficient and stable electrochromic supercapacitors. (16th July 2022) - Inamdar, Akbar I.; Chavan, Harish S.; Shin, Giho; Han, Jonghoon; Yeon, Seungun; Park, Sunjung; Patil, Supriya A.; Shrestha, Nabeen K.; Kim, Hyungsang; Im, Hyunsik
Summary: The combined features of functional electronic devices have attracted significant attention because of high demand for promising energy technologies. Of particular interest are electrochromic (EC) supercapacitors, which can visually display the level of stored energy in real‐time. Here, we demonstrate the EC energy storage properties of pure and doped Prussian blue (PB) thin films fabricated using electrodeposition. The pure PB films produced various colours at different potentials during their charging‐discharging cycles, but they suffered from instability. To overcome this, we doped PB films with ruthenium (Ru), iridium (Ir), and molybdenum (Mo). Of the doped specimens, the Mo‐doped PB films exhibited the most promising EC energy storage properties, with a specific capacity of 399.7 F g −1 at 1 A g −1, a colouration efficiency of 110.2 cm 2  C −1, and an excellent optical density difference of 0.92. The Mo‐doped PB films also demonstrated ultra‐fast colouration and bleaching behaviour within 3.25 and 4.04 seconds, respectively. Our experimental findings suggest that Metal‐doped PB films can be employed for practical application. Abstract : The combined features of functional electronic devices have attracted significant attention because of high demand for promising energy technologies. Of particular interest are electrochromic (EC) supercapacitors, which can visually display the level of stored energy in real‐time. Here, we demonstrate the EC energy storage properties of pure and doped Prussian blue (PB) thin films fabricated using electrodeposition.